Bayesian analysis of quark spectral properties from the Dyson-Schwinger equation - Fischer, Christian S.; Pawlowski, Jan M.; Rothkopf, Alexander; Welzbacher, Christian A. (Physical review, 2018)
We report results on the quark spectral function in the Landau gauge at - finite temperature, determined from its Dyson-Schwinger equation. - Compared to earlier quenched results, this study encompasses unquenched - Nf=2 +1 fermion flavors in the medium. For the computation of - real-time spectra, we deploy the recent Bayesian Reconstruction (BR) - method and develop a new prior in order to better assess the inherent - systematic uncertainties. We identify the quark quasiparticle spectrum - and analyze the (non)appearance of zero modes at or around the - pseudocritical temperature. In both, the fully unquenched system and a - simpler truncation, using a model for the gluon propagator, we observe a - characteristic two-peak structure at zero three-momentum. The - temperature dependence of these structures, in case of the gluon - propagator model, is different than observed in previous studies. For - the back-coupled and unquenched case, we find interesting modifications - at and around the pseudocritical transition temperature.